Teachers’ Reflection of Team-Teaching for Teacher Professional Development: A Phenomenological Study in a Primary School Context - Erlina; Somariah Fitriani; Hery Muljono (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: This study explores primary school teachers’ reflections on team-teaching as a professional development approach. Using a qualitative phenomenological method, eight teachers from a private Islamic primary school were selected through purposive sampling. Data were collected using reflective journals and analyzed through thematic analysis. The findings reveal eight benefits of team-teaching, including leadership support, improved teaching practices, collaboration, and student engagement. Four challenges were also identified: teacher chemistry, absenteeism, new methods, and professionalism. The study highlights the importance of leadership, peer mentorship, and structured support for effective team-teaching implementation Abstrak: Penelitian ini mengkaji refleksi guru sekolah dasar tentang pengajaran kolaboratif sebagai pendekatan pengembangan profesional. Menggunakan metode fenomenologis kualitatif, delapan guru dari sekolah dasar Islam swasta dipilih melalui sampling purposif. Data dikumpulkan melalui jurnal reflektif dan dianalisis menggunakan analisis tematik. Temuan menunjukkan delapan manfaat pengajaran kolaboratif, termasuk dukungan kepemimpinan, peningkatan praktik pengajaran, kolaborasi, dan keterlibatan siswa. Empat tantangan juga diidentifikasi: chemistry antar guru, absensi, metode baru, dan profesionalisme. Studi ini menyoroti pentingnya kepemimpinan, bimbingan sesama guru, dan dukungan terstruktur untuk implementasi pengajaran kolaboratif yang efektif.